2021
DOI: 10.7202/1083621ar
|View full text |Cite
|
Sign up to set email alerts
|

La croissance des villes canadiennes et australiennes guidée par le hasard ? Enjeux et mesure de la croissance aléatoire urbaine

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne. https://apropos.erudit.org/fr/usagers/politique-dutilisation/ Cet article est diffusé et préservé par Érudit.Érudit est un consortium interuniversitaire sans but lucratif composé de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…From data on French cities' population covering almost two centuries , Guerin-Pace (1995) rejected random growth based on a parametric approach. Finally, while Lalanne and Zumpe 1 (2020) confirmed that French cities observe random growth through a unit-root test, Lalanne and Zumpe (2019) also demonstrated that random growth processes can be very diverse (three processes at least) and that Gibrat's law is not the only stochastic process operating in urban systems. Nonetheless, departures from Zipf's and Gibrat's laws constitute exciting research perspectives and have been documented in the literature on urban economics by, for example, natural advantage locations or industrial composition among other things (Gabaix and Ioannides, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…From data on French cities' population covering almost two centuries , Guerin-Pace (1995) rejected random growth based on a parametric approach. Finally, while Lalanne and Zumpe 1 (2020) confirmed that French cities observe random growth through a unit-root test, Lalanne and Zumpe (2019) also demonstrated that random growth processes can be very diverse (three processes at least) and that Gibrat's law is not the only stochastic process operating in urban systems. Nonetheless, departures from Zipf's and Gibrat's laws constitute exciting research perspectives and have been documented in the literature on urban economics by, for example, natural advantage locations or industrial composition among other things (Gabaix and Ioannides, 2004).…”
Section: Introductionmentioning
confidence: 95%